(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the efficacy of coded herbal medicine (Hyprol) and losartan in hypertensive type II diabetic patients. Study Design: Case control study Place and Duration of Study: This study was carried out at the Out-patient Department of JPMC, Karachi and Herbal Clinics of Karachi from January 2014 to June 2014. Materials and Methods: This study is a case control prospective study to compare the effects of Losartan with herbal medicine (Hyprol) in type 2 diabetic hypertensive patients. 200 patients were enrolled and divided in two groups 'A' (Control group) & 'B' (Test group) treated with Losartan and Hyprol respectively. Results: With ARB (Losartan) baseline to final change for SBP as well as DBP was significantly reduced i.e. 22.45 %( p<0.001) and 16.84% (p<0.001) respectively and FBS was reduced by 21.85% (p<0.001) while Hyprol shows comparable results i.e. difference in SBP, DBP and FBS was 14 %( p<0.001), 15.31 %( p<0.001), 34.57% (p<0.001) respectively. Conclusion: ARBs are the first line drug of choice for hypertension since long time. Use of herbal medicine is an alternative mean of therapy to treat these patients and limit its cardiovascular and renal complications.